Hygienic significance of ambient air pollution with hydrogen sulphide emissions from pig-breeding complexes of high output (Environment & Health, 2017)
Objective: By means of field studies and questioning of the population, residing on the boundary of sanitary-and-protective zones (SPZ) of the pig-breeding complexes of high output we elaborated the complex procedure for the assessment of the effect of the ordour on the health of the population of residential area with the application of mathematical modeling of the pollution of atmospheric surface layer.Materials and methods: Hydrogen sulphide was taken as a target substance (the second risk class of chemical substances). It has one of the largest parts of atmospheric emissions from pig-breeding farms. The field studies of hydrogen sulphide concentrations in ambient air were performed at different distances (1000, 1500, and 2000 meters) from the stationary sources – pig-breeding farms.Assessment of the atmospheric emissions from the stationary sources for the period from 2012 to 2016 was carried with the help of ISC AIRMOD program.We prepared the questionnaire with a subjective assessment of the effect of hydrogen sulphide on the health of the population in the adjacent residential area and used the data of local medical institutions on the provision of medical care to the workers of these pig-breeding farms.Results: A tendency to a decrease of the level of hydrogen sulphide in the air as far as a distance from the source of pollution was detected in the study. But later on, it was found out that, in spite of the decrease of hydrogen sulphide dispersion in the air, in some cases the hydrogen sulphide concentration exceeded the standard concentrations.Furthermore, according to the data, there were the complaints about health deterioration in the workers of these farms and population of the residential area on the boundary of SPZ even when the hydrogen sulphide content was below the standard concentration in ambient air (0.008 mg / m3) and was at the level of ordour threshold (0.004 mg / m3).Conclusions: The procedure, proposed by us, can be used later on for the study of the changes in the calculation of regulatory sanitary-and-protective zones for similar enterprises and for the prevention of non-infectious diseases in the population of the residential area near pig-breeding complexes as well.
Keywords: pig-breeding complexes; ambient air; ordour; emissions